2022
DOI: 10.2174/1871520622666220408090541
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Epidermal Growth Factor Receptor Inhibitors (EGFRIs) and their Role in the Treatment of Cancer: A Review

Abstract: Tyrosine kinases are known to play a role in tumour growth and proliferation, and they have become common drug targets. Tyrosine kinase inhibitors (TKIs) prohibit associated kinases from phosphorylating tyrosine residues in their substrates, preventing downstream signaling pathways from being activated. Multiple robust and well-tolerated TKIs targeting single or multiple targets, including EGFR, ALK, ROS1, HER2, NTRK, VEGFR, RET, MET, MEK, FGFR, PDGFR, and KIT, have been developed over the last two decades, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…Four components targeting RTK signaling, axitinib, masitinib, OSI‐930, and pazopanib, were found to have preferential function in C2. Among the RTK signaling, PDGF/RTK and VEGF/RTK are closely related to tumorigenic growth processes, especially in promoting tumor angiogenesis, which was consistent with the invasive peculiarity of C2 [38]. Notably, five agents targeting proliferation were specifically designed for C3, including vorinostat inhibiting chromatin histone acetylation, cisplatin, cytarabine and TMZ inhibiting DNA replication, and MK‐2206 targeting PI3K signaling, which also coincide with the proliferative trait of C3.…”
Section: Resultsmentioning
confidence: 88%
“…Four components targeting RTK signaling, axitinib, masitinib, OSI‐930, and pazopanib, were found to have preferential function in C2. Among the RTK signaling, PDGF/RTK and VEGF/RTK are closely related to tumorigenic growth processes, especially in promoting tumor angiogenesis, which was consistent with the invasive peculiarity of C2 [38]. Notably, five agents targeting proliferation were specifically designed for C3, including vorinostat inhibiting chromatin histone acetylation, cisplatin, cytarabine and TMZ inhibiting DNA replication, and MK‐2206 targeting PI3K signaling, which also coincide with the proliferative trait of C3.…”
Section: Resultsmentioning
confidence: 88%
“…Non-small cell lung cancer (NSCLC) is the most common type of lung cancer, accounting for more than 80% of all cases 1 . Within the NSCLC patient population, the Epidermal Growth Factor Receptor (EGFR) has emerged as a promising therapeutic target 2 . EGFR mutations play a crucial role as oncogenic driver alterations in NSCLC, occurring in about 10–15% of cases among Caucasians and at a higher frequency of up to 50% among East Asians 3 .…”
Section: Introductionmentioning
confidence: 99%
“… 65 Since the threonine 790 gatekeeper residue controlled the inhibitor's affinity to the ATP binding pocket, this mutation improved ATP's affinity for the EGFR active site, preventing EGFR inhibition by first-generation EGFR inhibitors. 33 Subsequently, most clinical reports indicated that T790M accounted for half of the acquired resistant NSCLC cases to first-generation EGFR TKI. 66…”
Section: Introductionmentioning
confidence: 99%